Low Prevalence Of Cryptosporidium Parvum In Hospitalized Children In Kota Bharu, Malaysia - Menon, BS; Shukri Abdullah, MD; Mahamud, F; Morgan, UM; Malik, AS; Choo, KE; Balbir, Singh (UPM, 2001)
The aim of this prospective study was to determine the prevalence of Cryptosporidium parvum in hospitalized children in Kota Bharu, Malaysia. Over a 19 month study period, 258 stool samples were examined from 159 children; 109 with diarrhea and 50 controls without diarrhea. Modified Ziehl-Neelsen staining method and a polymerase chain reaction (PCR) assay were used to detect C. parvum and the samples were also examined for the presence of other intestinal parasites. Only 1 of the 109 (0.9%) children with acute diarrhea was positive for C. parvum by microscopy and PCR. Thirty-one percent of children were infested with other intestinal parasites, the most common being Ascaris lumbricoides and Trichuris trichiura. In conclusion, we found C. parvum to be an uncommon infective agent in hospitalized children with or without diarrhea in Kota Bharu, Malaysia.